Pesticide-induced epigenetic suppression of WNT signaling and NF-κB-driven inflammation impairs ovarian function in rats - Jan, Jasmeena; Sheikh, Wajid Mohammad; Gul, Shazia; Mohidin, Rumaisa; Bhat, Owais Mohmad; Lone, Mohammad Nadeem; Shah, Showkat Ahmad; Dar, Abid Hamid; Zargar, Mohammad Afzal; Bashir, Showkeen Muzamil; Wani, Nissar Ahmad (Food and chemical toxicology, 2025)
The study examined the impact of chlorpyrifos, dimethoate, and their co-exposure on ovarian structure and function in female Wistar rats. The study involved 24 rats, divided into four groups: control, chlorpyrifos (3 mg/kg), dimethoate (30 mg/kg), and combination. Histopathology revealed degenerated and atretic follicles, disorganized granulosa cells and cystic follicles in pesticide exposed rats. Hormonal analysis showed decrease in FSH, LH, PG, T and AMH and increase in ED levels. Gene expression studies revealed significant upregulation of ESR2 (∼2, ∼1.8, and ∼1.85 fold respectively) in chlorpyrifos, dimethoate and combination groups. In contrast, RSPO2, WNT7A, WNT3A and WNT5A were downregulated (reduced by ∼1.73–1.8, 1.7–2.6, 1.45–2.13 and 1.3–1.75 fold, respectively). The changes correlated with reduced β-catenin activation. DNA methylation analysis revealed an inverse correlation between methylation and gene expression, alongside upregulation of DNMT3A and DNMT3B (∼4.5, ∼2.1, ∼4.9; ∼3.75, ∼2.2, ∼3.8 fold in chlorpyrifos, dimethoate and combination groups respectively), suggesting methylation-mediated repression. Furthermore, enhanced expression of inflammation-related genes and cytokines, coupled with NF-κB activation, indicated significant inflammatory responses. Overall, the findings highlight gene specific DNA methylation and inflammatory disruptions in pesticide-exposed ovaries. However, the lack of ChIP assay limits confirmation of DNMT recruitment, which should be addressed in future studies. [Display omitted]